Crystal structure and Hirshfeld surface analysis of N-(2-(N-methylsulfamoyl)phenyl)formamide: Degradation product of 2-methyl-2H-1,2,4-benzothiadiazine 1,1-dioxide - Etse, Koffi Senam; Zaragoza, Guillermo; Pirotte, Bernard (European Journal of Chemistry, 2019)
The hydrolysis of 2-methyl-2H-1,2,4-benzothiadiazine 1,1-dioxide (2) during crystallization under humidity (85 %) conditions, lead to N-(2-(N-methylsulfamoyl)phenyl)formamide as second step hydrolysis product, identified in the proposed degradation mechanism. Crystal of N-(2-(N-methylsulfamoyl)phenyl)formamide C8H10N2O3S (4), was obtained and characterized. The molecular structure determination was carried out with MoKα X-ray and data measured at 100 K. The compound 4 crystallizes in triclinic P͞1 space group with unit cell parameters a = 4.8465(4) Å, b = 8.1942(9) Å, c = 11.8686(13) Å, α = 77.080(4)°, β = 82.069(4)°, γ = 80.648(4)°, V = 450.76 (8) Å3 and Z = 2. The crystal structure is stabilized by intramolecular N-H···O and intermolecular C-H···O and N-H···O hydrogen bonds that extended as infinite 1D chain along [100]. Stabilization is also ensured by oxygen-π stacking interaction between the aromatic ring and oxygen of the sulfonamide group. The analysis of intermolecular interactions through the mapping of dnorm and shape-index revel that the most significant contributions to the Hirshfeld surface 40.6 and 33.9% are from H···H and O···H contacts, respectively.